2002
DOI: 10.1055/s-2002-32658
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation and Chromogenic Assays of Factor VIII Activity: General Aspects, Standardization, and Recommendations

Abstract: Factor VIII (FVIII) is assayed by one-stage and two-stage clotting methods and by chromogenic methods, although the chromogenic method has largely replaced the two-stage clotting assay. Clinical plasma samples are assayed mostly by one-stage assays, but most manufacturers of concentrates use the chromogenic method, which is more precise and is the reference method of the European Pharmacopoeia and the International Society on Thrombosis and Haemostasis (ISTH). For most plasma-derived concentrates, assays again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
107
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 9 publications
6
107
0
5
Order By: Relevance
“…Since then the same trend has been found in almost every collaborative study, although the size of the discrepancy varies from study to study, and possibly with different types of concentrates [12].…”
Section: Plasma and Concentrate Units And In Vivo Recovery Of Fviiisupporting
confidence: 63%
“…Since then the same trend has been found in almost every collaborative study, although the size of the discrepancy varies from study to study, and possibly with different types of concentrates [12].…”
Section: Plasma and Concentrate Units And In Vivo Recovery Of Fviiisupporting
confidence: 63%
“…Serum levels of carcinoembryonic antigen (CEA) were measured using a chemiluminescent microparticle immunoassay with the ARCHITECT i2000SR system (Abbott Laboratories, Abbott Park, IL, USA). Plasma levels of fibrinogen (Clauss method) (17), D-dimer (immunoturbidimetric method) (18) and FVIII activity (coagulation method) (19) were measured using the Sysmex CS-5100 coagulation analyzer (Sysmex Corporation, Kobe, Japan), with the Dade ® Thrombin reagent, INNOVANCE ® D-Dimer and Coagulation Factor VIII Deficient Plasma (all from Siemens AG, Munich, Germany), respectively. Plasma levels of VWF and ADAMTS-13 were measured using the vWF ELISA kit and ADAMTS-13 ELISA kit (R&D Systems, Inc., Minneapolis, MN, USA), according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The chromogenic assays are generally based on indicators of activated factor X (FXa) enzymatic activity as a measure of FVIII cofactor activity on factor IX (FIX) [8,9]. A variety of studies have demonstrated that using the traditional calibrators, such as that provided by the International Society of Thrombosis and Hemostasis (ISTH), one-stage clotting assays underestimate plasma levels of FVIII by 20-50% when compared with chromogenic and immunological assays in severe haemophilia A patients infused with BDD-rFVIII [10][11][12], FVIII-deficient plasmas containing full-length rFVIII concentrates [13] or BDD-rFVIII [14,15].…”
mentioning
confidence: 99%
“…Moreover, the precision of chromogenic assays using predilution and 1% albumin in assay buffers, as recommended by the ISTH/Scientific and Standardization Committee [17], is superior to that of one-stage assays [8,15]. However, the use of chromogenic assays in patients receiving BDD-rFVIII raises some doubts from a clinical perspective, as the two different methodologies appear to reflect two faces of a haemostatic coin.…”
mentioning
confidence: 99%
See 1 more Smart Citation